Direct observation of cation distributions of ideal inverse spinel CoFe2O4 nanofibres and correlated magnetic properties. Issue 22 (22nd May 2017) - Zeng, Xue; Zhang, Junwei; Zhu, Shimeng; Deng, Xia; Ma, Hongbin; Zhang, Junli; Zhang, Qiang; Li, Peng; Xue, Desheng; Mellors, Nigel J.; Zhang, Xixiang; Peng, Yong
Abstract : An ideal inverse spinel structure of CoFe2 O4 nanofibres was observed by C s -corrected STEM and verified by their experimental and theoretical magnetic properties. Abstract : Low-dimensional spinel ferrites have recently attracted increasing attention because their tunable magnetic properties make them attractive candidates as spin-filtering tunnel barriers in spintronic devices and as magnetic components in artificial multiferroic heterostructures. Although we know that the distribution of cations (Fe 3+ and Co 2+ ) in a spinel structure governs its magnetic properties, their distribution in the so-called ideal inverse spinel structure of a ferrite, CoFe2 O4, has not yet been imaged with sub-ångstrom resolution. In this work, we fill this gap in evidence by reporting a direct observation of the distribution of cations in an ideal inverse spinel structure of CoFe2 O4 nanofibres using aberration-corrected transmission electron microscopy (TEM). The ordering of Co 2+ and Fe 3+ at the octahedral sites imaged along either [001], [011] or [−112] orientation was identified as 1 : 1, in accordance with the ideal inverse spinel structure. The saturation magnetisation calculated based on the crystal structure as determined from the TEM image is in good agreement with that measured experimentally on the spinel CoFe2 O4 nanofibres, further confirming results from TEM.